2019
DOI: 10.15587/1729-4061.2019.178937
|View full text |Cite
|
Sign up to set email alerts
|

Studying the operation of innovative equipment for thermomechanical treatment and dehydration of food raw materials

Abstract: The efficiency of technologies is defined in terms of product kinetics, energy intensity, and quality. The kinetic parameter of drying is the intensity of dehydration, the rate of drying, which is expressed in kg/s of removed moisture. Energy intensity is characterized by the amount of energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In the layer heater, TSs are set at an angle of 5°, the values of the heat transfer coefficients when flowing around the inclined pipe are higher due to more complete use of the pipe surface, mixing the flow. According to [8], TSs work most efficiently at an angle of inclination of 60°, but, due to the design features of the layer heater, it was not possible to use such an angle.…”
Section: Results Of Studying the Heat Transfer From The Condensation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the layer heater, TSs are set at an angle of 5°, the values of the heat transfer coefficients when flowing around the inclined pipe are higher due to more complete use of the pipe surface, mixing the flow. According to [8], TSs work most efficiently at an angle of inclination of 60°, but, due to the design features of the layer heater, it was not possible to use such an angle.…”
Section: Results Of Studying the Heat Transfer From The Condensation ...mentioning
confidence: 99%
“…Practically not considered are dryers that use water vapor as a heat carrier, applied for highly moist dispersed products, crops. The dryers provide high coefficients of heat transfer to the grain of 30...70 W/m 2 K [8]. Disadvantages: complicated structure, additional devices are needed for steam supply, condensate drainage.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Recently, studies of drying food raw materials in infrared, MW field are intensively carried out [20][21][22]. It was shown that the application of these methods provides intensification of transfer processes several times and sometimes by orders of magnitude.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It is shown that the drying rate is quite high, but the specific energy consumption for the process is not calculated and the task is not to study IR drying for grounds. Studies [10,11] show that the specific energy consumption for the convective drying process is from 5 MJ/kg to 9 MJ/kg and the discharge of waste coolant into the atmosphere.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%